2002
DOI: 10.1074/jbc.m205005200
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Phosphorylation of Kv1.2 Modulates Its Interaction with the Actin-binding Protein Cortactin

Abstract: Tyrosine phosphorylation evokes functional changes in a variety of ion channels. Modulation of the actin cytoskeleton also affects the function of some channels. Little is known about how these avenues of ion channel regulation may interact. We report that the potassium channel Kv1.2 associates with the actin-binding protein cortactin and that the binding is modulated by tyrosine phosphorylation. Immunocytochemical and biochemical analyses show that Kv1.2 and cortactin co-localize to the cortical actin cytoske… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 55 publications
2
73
0
Order By: Relevance
“…Therefore, the cortactin-Kv1.2 interaction appears to be maintained, albeit weaker, after channel endocytosis. This finding is consistent with biochemical studies showing that tyrosine phosphorylation of Kv1.2 reduces, but does not eliminate, cortactin binding (1).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Therefore, the cortactin-Kv1.2 interaction appears to be maintained, albeit weaker, after channel endocytosis. This finding is consistent with biochemical studies showing that tyrosine phosphorylation of Kv1.2 reduces, but does not eliminate, cortactin binding (1).…”
Section: Discussionsupporting
confidence: 82%
“…3). Data from previous studies (1) and Fig. 1 leading edge structures or vesicles revealed the most intense FRET signal at the leading edge, with significantly (P Ͻ 0.001, n ϭ 20) weaker FRET within vesicles (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We suppose that frequencies in the low and high ranges can be partly related to the cytoskeleton reorganizations that occur under the function of the ion channels and organelles movements [18]. Recently it was shown that cytoskeleton in its turn regulates ion channel activity and location of mitochondria and endoplasmic reticulum and Ca 2 signaling between them [19,20]. Further studies of neuron function by means of interference microscopy and doublewavelet analysis may help to reveal the relation of the cytoskeleton organization to the activity of the plasma membrane and cytoplasmic processes.…”
Section: Prl 94 218103 (2005) P H Y S I C a L R E V I E W L E T T E mentioning
confidence: 99%